Evaluasi Usabilitas Sebuah Situs Web Menggunakan Metode Cognitive Walkthrough - A'ang Subiyakto; Nurul Shifa; Ahmad Sulhi; Rumi Kamal; Muhamad Qomarul Huda (STMIK Sumedang, 2021)
Awareness of the importance of creating a broad business network awakens companies to make alliances with each other. One of the benefits of developing this network is to make the company more well-known so that the greater the number of partners, the greater the opportunity to enlarge the business. One of these strategies can be done with website development. However, most of these websites do not meet the expectations of interested parties, especially users. This study was conducted to evaluate the usability aspect of a website using the cognitive walkthrough method by involving its users. The purpose of this research is to identify and analyze what problems are faced by users when using the website that is the research sample and provide recommendations for improving the website interface. The results of this test show that there are still many problems that users encounter when using the sample website on the freelance, partnership, and internship menus.